PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS AUGMENTED REALITY PADA PEMBELAJARAN GEOGRAFI MATERI DINAMIKA LITOSFER - Bokingo, Muhamad Fachri; Rusiyah, Rusiyah; Nurfaika, Nurfaika; Lahay, Rakhmat Jaya; Hendra, Hendra (Universitas Negeri Makassar, 2023)
This study aims to develop Android- based Augmented Reality media for learning geography regarding lithospheric dynamics. This research is Research and Development (R&D) research using the ADDIE development model. There are 3 methods used in this research, namely observation, black box testing method, and finally the questionnaire method to obtain validation values and see the feasibility of the Augmented Reality media created. Validation is carried out by experts, materials, media experts and learning experts. After going through validation from experts, the media was then tested on students with a total of 22 students. The results of initial trials using the black box testing method show that the Augmented Reality media application runs well. The results of the material expert validation obtained a percentage value of 82% (valid value category). The validation value of media experts received a percentage value of 84% (valid value category). The learning expert validation received a percentage score of 93% (very valid score category) and the results of the student response questionnaire received a percentage score of 94.41% (very valid score category). Judging from the results of this assessment, it can be concluded that Augmented Reality-based learning media is suitable for use in the learning process.